The nature of Arctic polar vortices in chemistry-climate models - Mitchell, D; Charlton-Perez, A; Gray, L; Akiyoshi, H; Butchart, N; Hardiman, S; Morgenstern, O; Nakamura, T; Rozanov, E; Shibata, K; Smale, D; Yamashita, Y (2012)
The structure of the Arctic stratospheric polar vortex in three chemistry-climate models (CCMs) taken from the CCMVal-2 intercomparison is examined using zonal mean and geometric-based methods. The geometric methods are employed by taking 2D moments of potential vorticity fields that are representative of the polar vortices in each of the models. This allows the vortex area, centroid location and ellipticity to be determined, as well as a measure of vortex filamentation. The first part of the study uses these diagnostics to examine how well the mean state, variability and extreme variability of the polar vortices are represented in CCMs compared to ERA-40 reanalysis data, and in particular for the UMUKCA-METO, NIWA-SOCOL and CCSR/NIES models. The second part of the study assesses how the vortices are predicted to change in terms of the frequency of sudden stratospheric warmings and their general structure over the period 1960-2100. In general, it is found that the vortices are climatologically too far poleward in the CCMs and produce too few large-scale filamentation events. Only a small increase is observed in the frequency of sudden stratospheric warming events from the mean of the CCMVal-2 models, but the distribution of extreme variability throughout the winter period is shown to change towards the end of the twentyfirst century. © 2012 Royal Meteorological Society and British Crown, the Met Office.